MANAJEMEN KELAS DAN DAMPAKNYA TERHADAP EFEKTIFITAS PEMBELAJARAN MATA PELAJARAN FIQIH DI MADRASAH ALIYAH PARADIGMA PALEMBANG - Berlian, Zainal (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2019)
Effective teaching and learning process can be realized well if there is interaction between teacher and students, fellow students or with other learning resources. In other words, learning is said to be effective if there is a maximum interaction. Furthermore, maximum interaction will be easy to implement if the class and students are in a good arrangement or management. This management in the education literature is called class management. In other words, the effectiveness of learning is closely related to class management. To test this assumption the author conducted research at the Madrasah Aliyah Paradigm especially on fiqh subjects with the formulation of the problem as follows: 1. What are the procedures for Class Management in the Teaching and Learning Process Fiqh Subjects in the Palembang Paradigm of Palembang? 2. What is the impact of Class Management on the effectiveness of Teaching and Learning Fiqh Subjects in the Palembang Paradigm of Madrasah Aliyah? What factors can affect the effectiveness of the Teaching and Learning Process Fiqh Subjects in the Palembang Paradigm? This study uses a qualitative approach with a type of descriptive research. Acting as key informant is the deputy head of the curriculum, academic supervisors and 2 fiqh teachers. Then in the collection several techniques are used, namely observation (observation), interviews (interviews), and documentation studies. After the data is collected, it is then processed using qualitative descriptive techniques and deductive and inductive conclusions. Based on data analysis can be formulated several research conclusions as follows: 1. Class arrangement and organization of students in Islamic Jurisprudence Aliyah Paradigm class subjects are in accordance with classroom management procedures. Class Management Procedures in the Teaching and Learning Process subjects of jurisprudence in Aliyah Madrasas The Palembang paradigm is intended to begin with an increase in the awareness of educators as teachers. Then increase student awareness. Next is the introduction of student behavior. Making social contracts / class rules and setting alternative solutions through various approaches. 2. Class Management can improve the effectiveness of the Teaching and Learning Process subject of Fiqh in the Palembang Islamic Elementary School Paradigm, because it has fulfilled and has implemented the elements in the effectiveness of learning. 3. Factors that can affect the effectiveness of the Teaching and Learning Subjects of Fiqh in Aliyah Madrasas The Palembang paradigm consists of two factors (external and internal). External factors, including environmental factors and instrumental factors such as; curriculum, program/teaching materials, facilities and facilities, and the factors of the teacher itself. Internal factors, including the physiological and psychological conditions of students in the form of interests, talents and abilities possessed by each student.